Hubungan Antara Kepuasan Kerja Dengan Kinerja Karyawan Pada PT. Agrinusa Persada Mulia - Nurwijayanti Nurwijayanti (Musamus Journal of Business & Management, 2019)
Research objectives to prove the relationship between job satisfaction with employee performance at PT. Agrinusa Persada Mulia. It is a quantitative study based on empirical rational principles. Data was analyzed using the correlation of product moment from Pearson assisted SPSS 23. The research population is all employees of the administrative section of PT. Agrinusa Persada Mulia with 35 respondents. Test results prove there is a positive and significant relationship between job satisfaction with the employee's performance, with the number of correlation coefficient of (R) 0.773 with the number sig. 0.000 (P ˂ 0.05). The effective value of job satisfaction with the performance of the R Squer coefficient value is 59% then 41% that affects performance and not covered in research.